Georgetown Scientific Research Journal 2022
DOI: 10.48091/gsr.v2i2.42
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Effects of Frequency and Type of Physical Activity on Self-Esteem in Adolescent Males

Abstract: The goal of this study is to determine the effect of type and frequency of exercise on the self-esteem of college-aged males using a two-part online survey distributed amongst Georgetown students. Recent literature has investigated the implications of exercise on individuals’ self-perception, in which partaking in frequent endurance exercise is associated with higher levels of self-esteem. Consequently, my research group postulated that if male college students perform endurance exercise, rather than strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a longitudinal cohort study among kindergarten to fourth-grade females, Noordstar et al (2016) found that changes in global SE were significantly associated with perceived athletic proficiency and moderate-to-vigorous PA. Recently, Romero et al (2022) reported on the positive effects of endurance and strength exercises on SE in male college students. There was a statistically significant relationship between exercise frequency and SE, while the relationship between exercise type and SE was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal cohort study among kindergarten to fourth-grade females, Noordstar et al (2016) found that changes in global SE were significantly associated with perceived athletic proficiency and moderate-to-vigorous PA. Recently, Romero et al (2022) reported on the positive effects of endurance and strength exercises on SE in male college students. There was a statistically significant relationship between exercise frequency and SE, while the relationship between exercise type and SE was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal cohort study among kindergarten to fourth-grade females, Noordstar et al (2016) found that changes in global SE were significantly associated with perceived athletic proficiency and moderate-to-vigorous PA. Recently, Romero et al (2022) reported on the positive effects of endurance and strength exercises on SE in male college students. There was a statistically significant relationship between exercise frequency SE, while the relationship between exercise type and SE was not significant.…”
Section: Discussionmentioning
confidence: 99%